Effect of Conventional and Resin-modified Glass-Ionomer Liner on Dentin Adhesive Interface of Class I Cavity Walls After Thermocycling - Sampaio, P. C. P.; de Almeida Junior, A. A. [UNESP]; Francisconi, L. F.; Casas-Apayco, L. C.; Pereira, J. C.; Wang, L.; Atta, M. T. (Operative Dentistry Inc, 2011)
Objective: The aim of this in vitro study was to analyze the effect of glass-ionomer cement as a liner on the dentin/resin adhesive interface of lateral walls of occlusal restorations after thermocycling.Materials and Methods: Occlusal cavities were prepared in 60 human molars, divided into six groups: no liner (1 and 4); glass-ionomer cement (GIC, Ketac Molar Easymix, 3M ESPE) (2 and 5); and resin-modified glass-ionomer cement (RMGIC, Vitrebond, 3M ESPE) (3 and 6). Resin composite (Filtek Z250, 3M ESPE) was placed after application of an adhesive system (Adper Single Bond 2, 3M ESPE) that was mixed with a fluorescent reagent (Rhodamine B) to allow confocal microscopy analysis. Specimens of groups 4, 5 and 6 were thermocycled (5 degrees C-55 degrees C) with a dwell time of 30 seconds for 5000 cycles. After this period, teeth were sectioned in approximately 0.8-mm slices. One slice of each tooth was randomly selected for confocal microscopy analysis. The other slices were sectioned into 0.8 nun x 0.8 mm beams, which were submitted to microtensile testing (MPa). Data were analyzed using two-way ANOVA and Tukey test (p < 0.05).Results: There was no detectedstatistical difference on bond strength among groups (alpha < 0.05). Confocal microscopy analysis showed a higher mean gap size in group 4(12.5 mu m) and a higher percentage of marginal gaps in the thermocycled groups. The RNIGIC liner groups showed the lowest percentage of marginal gaps.Conclusions: Lining with RMGIC resulted in less gap formation at the dentin/resin adhesive interface after artificial aging. RMGIC or GIC liners did not alter the microtensile bond strength of adhesive system/resin composite to dentin on the lateral walls of Class I restorations.